HYdroxychloroquine to Improve Pregnancy Outcome in Women with AnTIphospholipid Antibodies (HYPATIA) Protocol: A Multinational Randomized Controlled Trial of Hydroxychloroquine versus Placebo in Addition to Standard Treatment in Pregnant Women with Antiphospholipid Syndrome or Antibodies - Schreiber, Karen; Breen, Karen; Cohen, Hannah; Jacobsen, Soren; Middeldorp, Saskia; Pavord, Sue; Regan, Lesley; Roccatello, Dario; Robinson, Susan E.; Sciascia, Savino; Seed, Paul T.; Watkins, Linda; Hunt, Beverley J. (Seminars in Thrombosis and Hemostasis, 2017)
Women with antiphospholipid antibodies (aPL) are at risk of adverse pregnancy outcomes, including recurrent first-trimester pregnancy loss and late pregnancy complications such as preeclampsia, HELLP (hemolysis, elevated liver enzyme levels, and low platelet levels) syndrome, premature delivery, intrauterine growth restriction, placental abruption, and intrauterine death. Current standard care in obstetric antiphospholipid syndrome includes aspirin and heparin and has resulted in live-birth rates of approximately 70%. However, 30% continue to have pregnancy complications. Hydroxychloroquine (HCQ) is suggested as a new treatment approach, but no randomized controlled trials (RCTs) have assessed its efficacy. This study aims to assess pregnancy outcome in women with aPL treated with HCQ versus placebo in addition to standard treatment. The HYdroxychloroquine to improve Pregnancy outcome in women with AnTIphospholipid Antibodies (HYPATIA) study is a phase IV multicenter RCT, in which pregnant women with persistent aPL will receive either HCQ or placebo in addition to their usual medication. The primary endpoint is a composite of aPL-related adverse pregnancy outcomes: one or more pregnancy loss(es) (either < 10 or > 10 weeks of gestation) and premature birth before 34 weeks due to any of the following preeclampsia, eclampsia, or recognized features of placental insufficiency. The HYPATIA study is expected to provide evidence on the effect of HCQ in pregnant women with persistent aPL.
Keywords: antiphospholipid antibodies; antiphospholipid syndrome; obstetric antiphospholipid syndrome; pregnancy; hydroxychloroquine